Disentangling the heterogeneous effects of different support policies on livestock and poultry farmers’ willingness to utilize manure resources: Evidence from central China - Xiaoke, Gu; Hongmei, Du; Khan, Jamal (Frontiers in Environmental Science, 2023)
China's livestock and poultry industries have undergone massive transformations, with far-reaching implications for resource consumption and environmental issues. Utilizing waste resources from livestock and poultry, which requires increased farmer participation, is critical for China to meet its goal of lowering carbon emissions while also advancing high-quality animal husbandry. This study developed a model based on stimulus-organism-response theory to explore the impact of different policy instruments on farmers' willingness to utilize resources, as well as effect of farmers' perception and the regulating effect of farmers' risk attitude and policy support. In doing so, it employs OLS and Bootstrap estimation on survey data from 607 farmers from 11 counties in China’s Hunan province. The study yielded the following main results. First, incentive policies have a significant positive effect on farmers' willingness to utilize resources. The service policy has the greatest positive impact among various incentive policies, followed by the subsidy policy, while the impact of the propaganda policy is insignificant. Second, farmers' perceptions mediate the effect of incentive policies on their willingness to utilize resources. Finally, risk attitude has a negative impact on farmers' willingness to utilize resources, indicating that the more conservative (riskier) a farmer's risk preference, the greater (smaller) the impact of farmers’ perception on willingness to utilize resources.